Corporate Branding: How Effective Is Internal Branding and How Does This Affect the Frontline Employees Performance - Mad Nor, Nazura (2008)
In the past decade, previous research has provided evidence on the important role that corporate brands play in providing company’s unique value proposition to external stakeholders and ensuring company’s sustainability in the long run. Nevertheless, they are still ongoing debates on successful corporate branding implementation. In this paper, a research study on frontline employees of a healthcare company is done to explore and understand the role of managers and HR in corporate branding, how effective is the internal branding implementation, and how does it affect the employees performance. The method used for this study is a mix of quantitative and qualitative research methodology. Selective employees are interviewed, and survey questionnaires are distributed to all the frontline employees in the company. Findings indicate that in order to build a positive attitudes and stronger personal involvement in the brand; the managers and HR need to work together to improve the implementation process on all the key elements of internal branding; recruitment, communications, and motivation.